Rapid and sensitive detection of enteroviruses in specimens from patients with aseptic meningitis. - Yerly, S (1996)
A 5-h PCR assay (Amplicor enterovirus test) was compared with viral culture for the detection of enteroviruses in cerebrospinal fluid. Of the cerebrospinal fluid specimens collected during a summer outbreak of aseptic meningitis, 34% were positive by viral culture whereas 66% were positive by the Amplicor PCR, suggesting that this technique improves the diagnosis of enteroviral meningitis.